Current Strategies and Applications for Precision Drug Design - Wang, Chen; Xu, Pan; Zhang, Luyu; Huang, Jing; Zhu, Kongkai; Luo, Cheng (Frontiers in Pharmacology, 2018)
In the context of the heterogeneity of individuals been uncovered by Human Genome Project (HGP), precision medicine that proposes the customized healthcare has become an intractable and hot research. Meanwhile, as the Precision Medicine Initiative launched, precision drug design aiming at maximizing therapeutic effects while minimizing undesired side effects for an individual patient has entered a new stage. The core of precision drug design is target based drug design. Once a disease related pathogenic key target is identified, rational drug design (also known as structure based drug design) which constitutes the major aspect of precision drug design can be performed. Examples of rational drug design including modulators design targeting on novel druggable targets and protein-protein interaction surface are summarized in this review. Besides, by virtue of the powerful ability in handling high-dimensional data and complex system, deep learning has efficiently promoted the applications of artificial intelligence in drug discovery and design. In this review, deep learning methods tailored to precision drug design are carefully discussed: genetic variants discovery and tumor neoantigen prediction. When a drug molecule is discovered, the development of specific targeted drug delivery system becomes another key aspect of precision drug design. Therefore, state-of-the-art techniques including antibody-drug conjugates (ADCs), and ligand-targeted conjugates are also included in this review.